What are the Opinions of Tax Administration Officials Regarding Tax Policy Reforms in Bosnia and Herzegovina? - LAZOVIC - PITA, Lejla; ŠTAMBUK, Ana (Journal of Advanced Research in Law and Economics, 2017)
The aim of this paper is to assess tax administration reforms in Bosnia and Herzegovina (BandH). After analyzing the three important preconditions for a successful tax administration reform in any (post transition) country which are all related to tax policy reform, namely, simplification of a tax system, a clear strategy and political commitment from the highest authorities, we firstly evaluated the success of tax policy reforms conducted in BandH so far. We conclude that all tax policy reforms in BandH were conducted inconsistently which is a result of a complex constitutional and political organization of BandH. Since the success of tax administration reforms relies on clear tax policy reforms, we assess the implementation of the tax policy reforms through a survey conducted among three groups of experts, namely, tax administration officials, the academia and the private sector. We have developed two benchmark theoretical models where one is more classical-interventionist and the other more neoliberal. We find that responses in all three groups are inconsistent in both theoretical benchmark models which confirm the inconsistency of tax policy and tax administration reforms in BandH.